ЭПИК АНЪАНАЛАР ТАЛҚИНИДА ИЖОДИЙ СИНТЕЗ МУАММОЛАРИ - Жумаева, С. (SCIENCE and SOCIETY, 2021)
The article depicts that the traditions of fairy tales are an important factor in the development of Uzbek and Karakalpak literature.It also discusses the concepts associated with the creation of stylistic forms of folklore as a result of the processing of the form, style of expression, image and motives of the fairy tale genre. The important role and significance of the factors and manifestations of stylization of folklore genres is studied in the development of Uzbek and Karakalpak literature.